Investigating English language teachers at tertiary level in adopting technological pedagogical content knowledge: Challenges in the 21st century - Yogi Widiawati (EduLite: Journal of English Education, Literature and Culture, 2022)
In this 21st century era, English teachers must have good knowledge of English as well as the skills of using various technology in order to make their teaching-learning process go smoothly. Nowadays, technology is like the primary need in every sector, especially in education sector. English lecturers should be able to adapt with the changes of teaching environment since the use of computers, laptops and other tools are becoming the big necessity in our daily life. There are three things that must be considered; technology, pedagogy and content knowledge. By understanding them, the teaching-learning process will become perfect. This article aims to find the perceptions of TPACK how it helps English lecturers achieve their goals. The data were taken from 3 English language lecturers of three different departments as the respondents. This mini research used descriptive quantitative in which the data were collected through observation and were analysed with data reduction, interpretation, and description. The findings shows that the score for content knowledge (CK) for all teachers ranges 78%-80 %, pedagogical knowledge (PK) ranges 55%-65%, technological knowledge (TK) ranges 60%-75%. Meanwhile score for Technological Content Knowledge (TCK) ranges 77%-82%, Technological Pedagogical Knowledge ranges (TPK) 60%-67%, TPACK 72%-75%. These imply that lecturers of polytechnics are good and skilful to integrate the technology with pedagogic and content knowledge.